Repeated Shocks and Preferences for Redistribution - Giovanni Gualtieri; Marcella Nicolini; Fabio Sabatini (Institute of Labor Economics (IZA), 2019)
A society that believes wealth to be determined by random "luck", rather than by merit, demands more redistribution. We present evidence of this behavior by exploiting a natural experiment provided by the L'Aquila earthquake in 2009, which hit a large area of Central Italy through a series of destructive shakes over eight days. Matching detailed information on the ground acceleration registered during each shock with survey data about individual opinions on redistribution we show that the average intensity of the shakes is associated with subsequent stronger beliefs that, for a society to be fair, income inequalities should be levelled by redistribution. The shocks, however, are not all alike. We find that only the last three shakes - occurred on the fourth and the eighth day of the earthquake - have a statistically significant impact. Overall, we find that the timing and repetition of the shocks play a role in informing redistributive preferences.
Keywords: H10; H53; D63; D69; Z1; 330; redistribution; inequality; natural disasters; earthquakes; multiple shocks